Gambaran Pemeriksaan Urea dan Kreatinin pada Penderita Arthritis Rheumatoid di Rumah Sakit Bhayangkara Makassar - Suharsi Tahir; Haswatun Hasanah (Jurnal Media Laboran, 2020)
Rheumatoid arthritis is an autoimmune disease in which the joints are symmetrically inflamed, causing swelling, pain and causing damage to the inside of the joint in question. Foods that are not good for people with rheumatoid arthritis are beef and butter, because these foods contain a lot of saturated fat. Urea is an important end product of nitrogen metabolism in humans or the end product of protein metabolism. While creatinine is a breakdown product of keratin. The amount of creatinine released by a person every day depends more on total muscle mass or protein metabolism rate. The purpose of this study was to describe the results of urea and creatinine examinations in patients with rheumatoid arthritis. sample. Furthermore, sampling using purposive sampling method, based on sample criteria. The last stage was the analysis of urea and creatinine with laboratory tests using the Dimension EXL 200 Full Automatic tool at Bhayangkara Hospital Makassar. The results showed the relationship or correlation between urea and creatinine was 0.184, the relationship was statistically significant with a significant value of 0.612. This illustrates that in patients with rheumatoid arthritis there is no increase or decrease in urea and creatinine levels.